2019
DOI: 10.1093/mnras/stz2363
|View full text |Cite
|
Sign up to set email alerts
|

What determines the sizes of bars in spiral galaxies?

Abstract: I use volume-and mass-limited subsamples and recently published data from the Spitzer Survey of Stellar Structure in Galaxies (S 4 G) to investigate how the size of bars depends on galaxy properties. The known correlation between bar semi-major-axis a and galaxy stellar mass (or luminosity) is actually bimodal : for log (M /M ) 10.1, bar size is almost independent of stellar mass (a ∝ M 0.1 ), while it is a strong function for higher masses (a ∝ M 0.6 ). Bar size is a slightly stronger function of galaxy halfl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…The conclusions from Sheth et al (2008) were subsequently partially questioned. In particular, Erwin (2018Erwin ( , 2019 argued that those conclusions may be affected by a detection problem. SDSS-based studies preferentially miss bars in lower mass, bluer, and gas-rich galaxies due to poor spatial resolution; instead, Erwin found that bars are as common in blue gas-rich galaxies as they are in red gas-poor galaxies using Spitzer data (Erwin 2018).…”
Section: Relations With the Galaxy Luminositymentioning
confidence: 99%
See 2 more Smart Citations
“…The conclusions from Sheth et al (2008) were subsequently partially questioned. In particular, Erwin (2018Erwin ( , 2019 argued that those conclusions may be affected by a detection problem. SDSS-based studies preferentially miss bars in lower mass, bluer, and gas-rich galaxies due to poor spatial resolution; instead, Erwin found that bars are as common in blue gas-rich galaxies as they are in red gas-poor galaxies using Spitzer data (Erwin 2018).…”
Section: Relations With the Galaxy Luminositymentioning
confidence: 99%
“…By performing a bi-dimensional decomposition on multiband SDSS images of 700 galaxies, Sanchez-Janssen & Gadotti (2013) found that barred discs tend to have fainter central surface brightness, and larger disc scalelengths h than unbarred galaxies of the same stellar mass (M * > 10 10 M ). Barred galaxies appear to be more extended than the unbarred counterparts (Erwin 2019). Consolandi (2016) found that massive spiral galaxies harbour red and dead bars, which become even redder with increasing galaxy mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This simplification brushes over the complexity and diversity of galactic morphologies, for example, the distinction between normal and barred spirals (Hubble 1926). Gadotti (2009), Weinzirl et al (2009), Salo et al (2015), and Erwin (2018Erwin ( , 2019 have considered more detailed models that decompose galaxies into three components: a disc, a bulge, and a bar if present. Despite the clear merit of such decompositions, this approach is possible only for relatively small samples of a few thousand nearby galaxies, such as the Spitzer Survey of Stellar Structure in Galaxies (S 4 G; Sheth et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is reasonable for us to neglect them in an article that is about stellar discs. 3 We acknowledge that a bar and a bulge are different dynamical entities, and that it is possible to separate in a morphological decomposition (Gadotti 2009;Weinzirl et al 2009;Salo et al 2015;Erwin 2018Erwin , 2019. We merely state that SAMs are not an appropriate tool for such decomposition.…”
Section: Introductionmentioning
confidence: 99%